Inhibition of Glutathione Synthesis Induced by Exhaustive Running Exercise via the Decreased Influx Rate of L-Cysteine in Rat Erythrocytes - Yanlian Xiong; Yanlei Xiong; Shuai Zhou; Zhenhai Yu; Dongmei Zhao; Zhiqiang Wang; Yuling Li; Jingtong Yan; Yu Cai; Wenqian Zhang (Cellular Physiology and Biochemistry, 2016)
Background/Aims: The main purpose of this study was to investigate the effect of exhaustive exercise on L-cysteine uptake and its effect on erythrocyte glutathione (GSH) synthesis and metabolism. Methods: Rats were divided into three groups: sedentary control (C), exhaustive running exercise (ERE) and moderate running exercise (MRE) (n=12 rats/group). We determined the L-cysteine efflux and influx in vitro in rat erythrocytes and its relationship with GSH synthesis. Total anti-oxidant potential of plasma was measured in terms of the ferric reducing ability of plasma (FRAP) values for each exercise group. In addition, the glucose metabolism enzyme activity of erythrocytes was also measured under in vitro incubation conditions. Results: Biochemical studies confirmed that exhaustive running exercise significantly increased oxidative damage parameters in thiobarbituric acid reactive substances (TBARS) and methemoglobin levels. Pearson correlation analysis suggested that L-cysteine influx was positively correlated with erythrocyte GSH synthesis and FRAP values in both the control and exercise groups. In vitro oxidation incubation significantly decreased the level of glucose metabolism enzyme activity in the control group. Conclusion: We presented evidence of the exhaustive exercise-induced inhibition of GSH synthesis due to a dysfunction in L-cysteine transport. In addition, oxidative stress-induced changes in glucose metabolism were the driving force underlying decreased L-cysteine uptake in the exhaustive exercise group.